Avaliação da rigidez arterial e comprimento de telômeros na artrite idiopática juvenil - Picarelli, Maria Mercedes Caracciolo (2016)
Introduction: Recent advances in juvenile idiopathic arthritis (AIJ) treatment promoted free disease survival. Cardiovascular disease (DCV) may emerge as an important cause of morbidity and mortality. Pulse wave velocity (VOP) and telomere length (TL) are considered as potential predictors of cardiovascular DCV. There are growing evidences of chronic and persistent inflammatory activity role on these processes. VOP and TL are potential early predictors of DCV and its outcomes. Objective: Access VOP and TL in a sample of AIJ patients, without cardiovascular risk factors, compare them with a group of healthy individuals sex and age matched and to test the correlation of these variables. Patients and Methods: 24 AIJ patients and 21 controls for TL and 20 controls for VOP were included. VOP was estimated by an oscillometric device (CardioSDyna – MAPA +). TL was accessed by polimerase chain reaction in real time (qPCR). Inflammatory activity was accessed by Juvenile Disease Activity Score (JADAS-27).Obesity, systemic hypertension, diabetes mellitus, impaired renal function and other inflammatory diseases were excluded. Results: Oligoarticular (65, 2%) and polyarticular subtypes were included, with 73,9% females and 82,6% were Caucasian. The average age was 15,5 + 6,3 years and the median disease duration was 9 [5-19] years. Between cases and controls for LTL there was significant difference in age no differences in sex, ethnics and BMI. The JADAS median was 8 [0, 00 – 20, 1], considered active when above 1, 0. PWV was normal in all patients, JIA and control (5.1 + 0.20 m/s vs. 4.98 + 0.06 m/s, P = 0, 66). TL expressed by T/S ratio (amplification telomere product and single copy gene) was significantly reduced between JIA patients and controls (0. 85 + 0, 34 vs. 1, 67 + 1, 38, Mann-Whitney test P = 0.025). When age adjusted by ANCOVA, the difference remained significant (P= 0,032). There was no correlation between TL and age (P =0, 449, r=0, 166), sex (P=0, 521), disease duration (P =0, 358, r=-0, 318), JADAS (P = 0, 184, r=-0, 287) e VOP (P = 0, 843, r=0, 044) in patients with AIJ. Conclusions: TL was significantly shorter in long disease duration and high to moderate disease activity with no DCV risk factors AIJ patients and compared to controls.VOP was normal and no significant difference between controls were found. No correlations were observed between TL or VOP and disease duration, age and sex.